The Influence of Brand Loyalty and Price Perception on NCT Photocard Purchase Intention (Case of Indonesian Sell-buy-trade Community) - Dameria Cathrine; Djoko Setyabudi; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2023)
With the advancement of the digital age, online entertainment and commerce have become even more enmeshed in daily activities. The influence of South Korean entertainment is obvious across many sectors, including consumer purchases of Korean items and services. NCT, like every other group, draws a crowd in the form of musical works as well as diverse goods. The primary object of this study, photocards, is among the most valuable collectibles and is just as significant as albums. Utilising idol worship to increase the pleasant perception that a certain brand has in consumers’ thoughts and convince them to choose that brand has evolved into a crucial marketing strategy for many businesses. Price is also the main factor influencing consumers intention to make a purchase. The purpose of this study is to shed light on how brand loyalty and price perception influence the interest of purchasing NCT photocards. This research is a quantitative research with explanatory method. The theory applied in this study is the Theory of Reasoned Action, and non-probability sampling was employed as the sampling method. One hundred NCT fans who fit the profile of the sample are between the ages of 18 and 23. All validity, reliability, and classical assumption tests were deemed to be valid. Using 2 multilinear regression, result shows that the hypothesis is accepted with significance value of 0.000.